(3GdhUjIs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3SHMGf GdChd bHd cd TF hGdCNQ HYO cd TF s
(3BNQgG (B:s
(3hdef JbOefG ef GdadGSaI JeJ GdQSGdI GdehSheI HGdhUjI ai eUfaGJ LGHQ Hf MjGf Gdchai s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs